Effects of B4C particle size on the microstructures and mechanical properties of hot-pressed B4C–TiB2 composites. Issue 17 (1st December 2018) - Liu, Zetan; Deng, Xiangong; Li, Jiamao; Sun, Yaxin; Ran, Songlin
Abstract: Full dense B4 C–30 vol% TiB2 composites were prepared by hot pressing at 2000 °C under 35 MPa from four different starting B4 C powders with their medium particle sizes ranging from 0.5 to 35.8 µm. The effects of B4 C particle size on the microstructures and mechanical properties of composites were investigated. The results indicated that both B4 C and TiB2 grains grew during sintering process, and each kind of grains had a pinning effect on the grain growth of the other. With coarse B4 C powders as raw materials, TiB2 grains in obtained B4 C–TiB2 composites tended to grow with the [001] zone axis parallel to the applied pressure direction, which possibly reinforced the composites. When the particle size of the starting B4 C powder was 7.09 µm, the obtained B4 C–TiB2 composite exhibited the optimized mechanical properties including a flexural strength of 754 MPa, a Vicker hardness of 30.01 GPa and a fracture toughness of 5.23 MPa m 1/2, respectively, due to the most homogenous and finest microstructures.